The Migrations of Engineers and Entrepreneurs at the Time of the “Industrial Revolution(s):” Forced Migrations or Opportunities? - Nachez , Pascale (Sensus Historiae, 2024)
In the eighteenth and nineteenth centuries, economic migration, often caused by war, epidemics and famine, led to a high level of labour emigration in a Europe undergoing rapid transformation. We study the mobility of labour and training in the textile industry, particularly between Lancashire (Manchester), Alsace (Mulhouse), Saxony (Chemnitz) and the Kingdom of Poland (Łódź). We note that these migrations, whether permanent or not, reflect the international development of companies and the individual careers of technicians, engineers and entrepreneurs, which we see in other forms today. These migrations are often linked to areas of innovation, such as Manchester for mechanical engineering and Mulhouse for chemicals. For textile workers, migration was more regional a border-based than international, and the gradual improvement in working and living conditions encouraged them to settle permanently in the host country.